Reasons that determine the practice of football in athletes of the sub-15 and sub-17 categories of a team of the country of State of Sao Paulo - Carvalho, Bruno Jacob de [UNESP]; Maffei, Willer Soares [UNESP]; Monesso, Cesar Torino [UNESP]; Lopes Verardi, Carlos Eduardo [UNESP] (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2018)
Football is a popular sport both in Brazil and the world, and considering the huge number of people who practice it or want to make a living playing it, it's fundamental to know what motivates the athletes to practice it during the process of forming new athletes, in order to proceed in a manner as to avoid that they will quit it. This study purpose was to analyze quantitatively the motivation of sub-15 and sub-17 football athletes from the team of the town of Mirassol, in the state of Sao Paulo. The Brazilian version of the SMS (Sport Motivation Scale) was used. It contains 28 items divided in seven subscales: amotivation, extrinsic motivation - external regulation, extrinsic motivation - introjected, extrinsic motivation - identified, intrinsic motivation - to experience stimulation, intrinsic motivation - to accomplish and intrinsic motivation - to know. The results showed that the athletes are more intrinsic motivated to know the sport (5.45 +/- 1.40) comparing to other types. However, there are findings of high scores in amotivation, statistically similar to MI-C (p=0.111), what is concerning because they are related to performance and continuity in practice. Therefore, it's necessary to provide psychological support for the athletes, those in formation and the professional ones.
Keywords: Football; Motivation; Basis category